ANALISIS PERBANDINGAN HASIL BELAJAR MAHASISWA BERDASARKAN JALUR MASUK PERGURUAN TINGGI PADA MAHASISWA PENDIDIKAN EKONOMI ANGKATAN 2012 DAN 2013 UNIVERSITAS RIAU - Sarmaulina Sihite; Gimin '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstack: Selection is a process to produce students college who are required in accordance with the prescribed criteria and categories for each University/College concerned. College selection is itself a national selection for new students at each College of both public and private. Due to some of the students accepted out of the selection that has been set is not able to achieve maximum learning outcomes, resulting in generalization to outcomes learning. In this study aims to compare student results based selection College on Economic Education Study Program in forces 2012 and 2013 University of Riau. This research is located in the program studies economic education Faculty of Teaching and Education University of Riau. Data obtained from Riau University Computer Center in the form of IP (Index Ratings) student college from 2012 and 2013. The technique used is purposive sampling so that the sample amounted to 170 people. The analysis used was ANOVA (Analysis Of Variance) to see the difference in student college learning outcomes by the selection. From the results of the analysis, there is a significant difference between the results of study by that is the path Sign SNMPTN Invitation, SNMPTN Written/SBMPTN, PBUD, and Independent. From the above results need to be taken into consideration to the team selectors nationally and team selectors local (University) in determining the selection tools are qualified and screening prospective students who will be admitted to the University is able to compete, ready to learn, achieve maximum learning results and master their fields respective.Keywords: Entrance in Higher Education and Learning Outcomes